Justification of education market characteristics - Малюкіна, Анастасія Олександрівна (Technology audit and production reserves, 2014)
Despite the large number of discussions of various scientists and economists in the field of education for young people, still little attention has been paid to the market of education services. In this paper, the author presents characteristics of the market of education services with respect to higher educational institutions of Ukraine. The main purpose of the research is to study theoretical and methodological approaches relative to the market of education services. The basic concepts are formulated and defined, namely, “market”, “education service”, “market of education services.” In addition, participants of the education service market are analyzed and summarized, which is divided into generally accepted and offered participants of these services. Also, special attention is paid to the peculiarities of the market of education services. The developments presented in this paper are used in the learning process in studying the course “Personnel Management”.